Phenotypic comparison and the potential antitumor function of immortalized bone marrow-derived macrophages (iBMDMs) - Xie, Dong-kun; Yao, Jin; Li, Peng-hui; Zhu, Yan-wen; Chen, Jia-nuo; Cao, Xiu-li; Cheng, Shi-lin; Chen, Ya-miao; Huang, Yi-fei; Wang, Liang; Wang, Zan-han; Qiao, Rong; et al. (Frontiers in Immunology, 2024)
Macrophages are an important component of innate immunity and involved in the immune regulation of multiple diseases. The functional diversity and plasticity make macrophages to exhibit different polarization phenotypes after different stimuli. During tumor progression, the M2-like polarized tumor-associated macrophages (TAMs) promote tumor progression by assisting immune escape, facilitating tumor cell metastasis, and switching tumor angiogenesis. Our previous studies demonstrated that functional remodeling of TAMs through engineered-modifying or gene-editing provides the potential immunotherapy for tumor. However, lack of proliferation capacity and maintained immune memory of infused macrophages restricts the application of macrophage-based therapeutic strategies in the repressive tumor immune microenvironment (TIME). Although J2 retrovirus infection enabled immortalization of bone marrow-derived macrophages (iBMDMs) and facilitated the mechanisms exploration and application, little is known about the phenotypic and functional differences among multi kinds of macrophages. In this study, we demonstrated iBMDMs exhibited the features of rapid proliferation and long-term survival. We also compared iBMDMs with RAW264.7 cell line and mouse primary BMDMs with in vitro and in vivo experiments, indicating that the iBMDMs could undergo the same polarization response as normal macrophages with no obvious cellular morphology changes after polarization. What's more, iBMDMs owned stronger phagocytosis and pro-apoptosis functions on tumor cells. In addition, M1-polarized iBMDMs could maintain the anti-tumor phenotypes and domesticated the recruited macrophages of receptor mice, which further improved the TIME and repressed tumor growth. In summary, iBMDMs can serve as a good object for the function and mechanism study of macrophages and the optional source of macrophage immunotherapy.